PENERAPAN KEGIATAN ECOBRICK DALAM PENDIDIKAN KARAKTER PEDULI LINGKUNGAN DAN KREATIF MELALUI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SD NEGERI 10 RAMBUTAN - Cahyani, Ade; Treny Hera; Sonia Anisah Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of Ecobrick activities in instilling environmental care and creativity character education through the Strengthening the Profile of Pancasila Students Project (P5) at SD Negeri 10 Rambutan. The background of this research is the issue of plastic waste in the school environment, which requires creative and educational solutions. The Merdeka Curriculum, through P5, serves as a strategic medium to address this issue using a Project-Based Learning approach. This research employs a descriptive qualitative method, with data collection techniques including observation, interviews, questionnaires, and documentation. The research subjects were teachers and fifth-grade students in the even semester of the 2024/2025 academic year. The results indicate that  Ecobrick activities not only help reduce plastic waste but are also effective in fostering students' environmental awareness and creativity. This project facilitates students in thinking critically, collaborating, and producing meaningful and useful creations. Therefore, implementing  Ecobrick as part of the P5 project offers a meaningful and contextual learning alternative aligned with the goals of the Pancasila Student Profile.